Studies on ethoxylated phenolic resins. Part. I. Surface characteristics and properties of coatings on metal - Mohamed, A.S.; Mohamed, M.Z.; Sadek, E.M.; Motawie, A.M. (Polimery, 2022)
Phenolic resins such as resol or novolac phenol-formaldehyde (PF) ones have been synthesized and etherified with poly(ethylene glycol) (PEG) with different molecular weights (1000, 1500, 4000). The solution behaviors in aqueous medium of the prepared resol and novolac phenol-formaldehyde ethoxylated resins, as nonionic polymeric surfactants with different hydrophilic chains lengths, have been interpreted. Surface and interfacial tension measurements as well as emulsifying power and foaming properties of the tested nonionic polymeric surfactants were studied. The critical micelle concentration (CMC) and the value of free surface energy reached at this concentration gamma(CMC) were also measured. Coatings on metal, made of the investigated phenolic ethoxylated resins, were prepared and evaluated as varnishes. This study indicated that the free surface energy of the prepared nonionic polymeric surfactants as well as the ease of formation of aggregates increase with PEG hydrophilic chain length increasing. Also, it was found that coating compositions based on resol PF ethoxylated resins with PEG-4000 offer chain flexibility and excellent coating properties.